2017
DOI: 10.1007/s00540-017-2346-y
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane in patients at risk of ventricular dysrhythmias

Beny Charbit

Abstract: Terao et al. In these patients, propofol should be preferred, without sevoflurane, for both induction and maintenance of anesthesia [5], especially as the present work confirms the good electrophysiological tolerance of propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…I wish to thank Dr. Charbit for his comments [1] on our recent article [2]. I address his comments here.…”
Section: To the Editormentioning
confidence: 96%
“…I wish to thank Dr. Charbit for his comments [1] on our recent article [2]. I address his comments here.…”
Section: To the Editormentioning
confidence: 96%
“…In previous studies, majority of experts consider that sevo urane prolonged the QTc interval signi cantly and increased the risk of ventricular arrhythmia. [5][6][7] It also has been reported that sevo urane prolong the QT interval without affecting the Tp-e interval or QT interval. [8][9][10] Therefore, nding an e cient biomarker that can correctly evaluate the effects of sevo urane or other drugs on cardiac electrophysiology has a great importance in clinical.…”
Section: Introductionmentioning
confidence: 99%